(untitled) (Journal of Asian Development Studies, 2025)
Entrepreneurial intention among university students has garnered increasing scholarly attention due to its potential to drive innovation, foster self-employment, and promote economic development, particularly in developing countries like Pakistan. In this respect, family support and entrepreneurial education are regarded as antecedents to influence the aspirations and willingness of people to become entrepreneurs. Nonetheless, the factors influencing entrepreneurial intention are not very well-examined. The purpose of this study is to investigate the direct impact of entrepreneurial education and family support on entrepreneurial intention, and to explore the mediating roles of self-efficacy and attitude toward entrepreneurship. The research design employed a quantitative and cross-sectional approach. The survey was used to gather data through structured questionnaires, which were completed by a sample size of 341 university-going students in private sector universities within the province of Punjab, Pakistan. A structural equation model (SEM) analysis was conducted using SmartPLS 4.0 to examine the direct and indirect relationships between the variables. Results show that entrepreneurial education and family support have no direct effect on students’ entrepreneurial intentions; however, they do have an indirect effect through their impact on self-efficacy and attitude.